Optimal energy resource mix for the US and China to meet emissions pledges. (15th March 2019) - Anasis, John G.; Khalil, Mohammad Aslam Khan; Butenhoff, Christopher; Bluffstone, Randall; Lendaris, George G.
Highlights: Reducing coal use is key for both nations to meet their emissions targets. Increased energy efficiency and electric vehicle usage are among the lowest cost strategies. Both nations could meet their targets without increased use of nuclear power. Large scale tree planting only provides a marginal benefit. Abstract: The emissions pledges of the US and China as outlined in their November 2014 agreement and in the Paris Climate Accord are key aspects of global efforts to reduce greenhouse gas emissions. A number of major US states are still pursuing emissions goals aligned with these targets even though the Trump Administration has withdrawn the US from the Paris Accord. China has also reaffirmed its commitment to its targets. This raises the question of what would be the optimal mix of energy resources each nation should deploy in order to meet its respective target. We examine this question using the Combined Energy and Geoengineering Optimization Model (CEAGOM). Our analysis shows that both nations would need to make significant but achievable adjustments to their respective energy mixes in order to meet their targets.